Production of marketable milk in the sub-humid tropics: experiences, lessons and technologies from coastal Kenya - Thorpe, W.R.; Maloo, S.H.; Muinga, R.W.; Mullins, G.R.; Mureithi, J.G.; Njunie, M.; Ramadhan, A. (Food and Agriculture Organization of the United Nations, 1995)
The Kenya coastal region has a large, unsatisfied market for milk and dairy products. Between 1988 and 1994, a research project, closely linked to extension, identified and addressed technical constraints that limit smallholder dairy Development in the region. Methodological approaches are outlined. Smallholders found it difficulty to maintain the advantages of systematic crossbreeding. Research showed that rotational crossing was appropriate when AI is available. In its absence, crossbred bulls should be considered. A study of lifetime productivity demonstrated the major contribution that genetic improvement can make to increasing productivity. Systematic epidemiological studies identified East Coast fever (ECF) as the cause of serious production losses. The infection and treatment method of immunization was more effective than current control methods, and was accepted by smallholders. Compared to recommended practises, intercropping with legumes, and manure and legume mulch application, improved year - round feed availability for dairy cows. Feeding legume and maize bran supplements was very cost-effective. Through collaborative research-extension activities, legume technologies were extended to many smallholdings. The linkages with farmers will facilitate the Development and testing of other technologies. Finally, the importance of a favourable operational environment for smallholders is emphasised, including institutional structures to encourage effective research- extension- farmer linkages and policies to facilitate dairy market Development.